Recovery of valuable metals from waste printed circuit boards using organic acids synthesised by Aspergillus niveus - Santhosh Krishnamoorthy; Gnanasekaran Ramakrishnan; Balaji Dhandapani (IET Nanobiotechnology)
Abstract Organic acids such as citric acid, itaconic acid and oxalic acid synthesised by Aspergillus niveus were used for the bioleaching of metals from waste printed circuit boards. Bioleaching of valuable metals was performed in one‐step, two‐steps and spent medium approaches using A. niveus. In the absence of waste printed circuit boards (WPCBs), the dry cell weight of A. niveus was higher when compared with the presence of WPCBs. Variations in the dry cell weight were observed for the presence of different particle sizes. The increase in itaconic acid and oxalic acid synthesis was found at a reduced particle size (60–80 mesh) and reached the maximum titre of itaconic acid (22.35 ± 0.87 mM) and oxalic acid (12.75 ± 0.54 mM) in 12 days during the two‐step bioleaching. The maximum recovery of 75.66% Zn, 73.58% Ni and 80.25% Cu from WPCBs was achieved in 15 days in two‐step leaching with particle sizes of the mesh being 60–80.